THE DETERMINATION OF AN OPTIMAL RETENTION OF AN EXCESS OF LOSS EARTHQUAKE REINSURANCE (CASE STUDY: DKI JAKARTA) - Adnan Musthafa, Rayhan
According to the Fiscal Policy Agency of the Ministry of Finance of the Republic of Indonesia (2018), earthquakes cause annual losses, on average, of 7.56 trillion rupiah. Insurance and reinsurance are two of the means to reduce the risk of financial losses due to earthquakes. One type of reinsurance scheme is an excess of loss reinsurance. This type of reinsurance protects an insurance company against financial losses which exceed a certain value, called a retention. One method to determine the amount of a reinsurance premium is the Expected Value Premium principle. In an excess of loss reinsurance scheme, a low retention value results in a low insurance company’s liability, but a high reinsurance premium. Meanwhile, a high retention value results in a low reinsurance premium, but a high insurance company’s liability. As a result, it is important for an insurance company to be able to determine an optimal retention for the corresponding reinsurance scheme. In this final project, financial losses due to earthquakes on residential data in DKI Jakarta are modeled using an Earthquake Catastrophe (CAT) model. Using Monte Carlo simulations, the Average Annual Loss (AAL) produced by an Event Loss Table (ELT) in an Earthquake CAT Model is used to generate an annual Total Aggregate Losses data which is assumed to follow some probability distributions. An optimal retention is determined using the Value-at-Risk (VaR) risk measure. Several excess of loss reinsurance schemes are given based on several values of VaR with the corresponding optimal retentions.